2005
DOI: 10.1074/jbc.m503934200
|View full text |Cite
|
Sign up to set email alerts
|

Periplasmic Protein HdeA Exhibits Chaperone-like Activity Exclusively within Stomach pH Range by Transforming into Disordered Conformation

Abstract: The extremely acidic environment of the mammalian stomach, with a pH range usually between 1 and 3, represents a stressful challenge for enteric pathogenic bacteria such as Escherichia coli before they enter into the intestine. The hdeA gene of E. coli was found to be acid inducible and was revealed by genetic studies to be important for the acid survival of the strain. This study was performed in an attempt to characterize the mechanism of the activity of the HdeA protein. Our data provided in this report str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
212
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(219 citation statements)
references
References 27 publications
7
212
0
Order By: Relevance
“…In vitro studies demonstrated that at neutral pH, HdeA is a well-folded dimer with no chaperone activity (4). Upon exposure to low pH, HdeA, like many other proteins, loses structure (6,7). However, in contrast to most other proteins, which are inactivated upon pH-induced unfolding, partial unfolding and dissociation of HdeA into monomers causes the activation of its chaperone function (4,7).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro studies demonstrated that at neutral pH, HdeA is a well-folded dimer with no chaperone activity (4). Upon exposure to low pH, HdeA, like many other proteins, loses structure (6,7). However, in contrast to most other proteins, which are inactivated upon pH-induced unfolding, partial unfolding and dissociation of HdeA into monomers causes the activation of its chaperone function (4,7).…”
mentioning
confidence: 99%
“…Upon exposure to low pH, HdeA, like many other proteins, loses structure (6,7). However, in contrast to most other proteins, which are inactivated upon pH-induced unfolding, partial unfolding and dissociation of HdeA into monomers causes the activation of its chaperone function (4,7). We recently reported that low pH induces the exposure of structurally plastic, high-affinity binding sites for unfolding proteins on HdeA, and enables it to effectively prevent protein aggregation in vitro (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both chaperones are only active below pH 3 and prevent irreversible aggregation of acid-denatured periplasmic proteins (14,21,23,28). HdeA seems to play a major role at pH 2, whereas HdeB is more active at pH 3 (23).…”
mentioning
confidence: 99%
“…Some of the best-characterized systems involve amino acid decarboxylases, which consume protons during amino acid decarboxylation, and antiporters that exchange product for substrate (29). Finally, DNA repair systems (10,81,82) and chaperones (8,31,41,46,50) appear to be important for the reparation of cellular material damaged by exposure to acid.…”
mentioning
confidence: 99%